2(3x-1)=11+(8-x)

Simple and best practice solution for 2(3x-1)=11+(8-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-1)=11+(8-x) equation:


Simplifying
2(3x + -1) = 11 + (8 + -1x)

Reorder the terms:
2(-1 + 3x) = 11 + (8 + -1x)
(-1 * 2 + 3x * 2) = 11 + (8 + -1x)
(-2 + 6x) = 11 + (8 + -1x)

Remove parenthesis around (8 + -1x)
-2 + 6x = 11 + 8 + -1x

Combine like terms: 11 + 8 = 19
-2 + 6x = 19 + -1x

Solving
-2 + 6x = 19 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-2 + 6x + x = 19 + -1x + x

Combine like terms: 6x + x = 7x
-2 + 7x = 19 + -1x + x

Combine like terms: -1x + x = 0
-2 + 7x = 19 + 0
-2 + 7x = 19

Add '2' to each side of the equation.
-2 + 2 + 7x = 19 + 2

Combine like terms: -2 + 2 = 0
0 + 7x = 19 + 2
7x = 19 + 2

Combine like terms: 19 + 2 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 10(x+2)+6=96 | | 3x-5=12-4x | | 5x^2=41x-8 | | 13+3(4r-3)=-8 | | 35x^2y-21xy-28x= | | 3888.21=12.117x^2-233.406x+1765.675 | | 2x^2+24=x^2-11x | | 42+73+137= | | 11x-6x-6=20-8x | | x^2-4x-77= | | 18-2(3p+5)=136+4(p-2) | | 5p-6=-31 | | cx+ax=b | | 6y+2-4y=-18 | | y-4=-7(x+2) | | 27pq+45p^2= | | H-2h+4=10 | | -3xy^2(6xy^2+6xy-3x)= | | 2h+h+4=10 | | X^3-7x^2+9x-63=0 | | x+x+8= | | 12+3(2y-5)=25+4y | | m+8n-5m-3n= | | P-6=24-2P | | 2x+24=0.285 | | -ax=b | | 2x+24=0.28 | | 8x+65-5x-75=35-63x | | 3x^4+9x^2+6=0 | | s=(4000)+71 | | 120overn=10 | | p(x)=-13x^2+1430x-23.400 |

Equations solver categories